Evaluation of a communication skills program for first-year medical students at the University of Toronto - Shapiro, Solomon M (BioMed Central, 2009)
BACKGROUND: Effective doctor-patient communication has been linked to numerous benefits for both patient and physician. The purpose of this study was to evaluate the effectiveness of the University of Toronto's Therapeutic Communication Program (TCom) at improving first-year medical students' communication skills. METHODS: Data were collected during the 1996/97, 1997/98, 1998/99 and 1999/00 academic years. The study used a repeated measures design with a waiting list control group: students were randomly assigned to groups starting the educational intervention in either September (N = 38) or February (N = 41), with the latter being used as a control for the former. Communication skills were assessed at the pre- and post-intervention times and at the end of the academic year from the perspectives of student, standardized patient and external rater. RESULTS: Only the external rater, using an instrument designed to assess the students' empathy based on their written responses, showed a time × group interaction effect (p = 0.039), thereby partially supporting the hypothesis that TCom improved the students' communication skills. Students rated themselves less positively after participation in the program (p = 0.038), suggesting that self-evaluation was an ineffective measure of actual performance or that the program helped them learn to more accurately assess their abilities. CONCLUSION: The lack of strong findings may be partly due to the study's small sample sizes. Further research at other medical or professional schools could assess the effectiveness of similar courses on students' communication skills and on other capacities that were not measured in this study, such as their understanding of and comfort with patients, their management of the doctor-patient relationship, and their ability to give and receive feedback.